Research Progress on the Use of the Traditional Chinese Formula Si-Jun-Zi Tang in the Prevention and Treatment of Schizophrenia - Ma, Teng (International Journal of Pharmaceutical Investigation, 2026)
Schizophrenia is a chronic and severe psychiatric disorder characterized by positive symptoms, negative symptoms, and cognitive deficits, imposing profound burdens on patients, families, and healthcare systems worldwide. Despite the central role of antipsychotic medications, they remain limited in efficacy against negative and cognitive symptoms, and are frequently associated with adverse effects and treatment resistance. Traditional Chinese Medicine (TCM) offers a complementary therapeutic avenue. This review aims to systematically examine the potential of Si-Jun-Zi Tang (SJZT), a canonical TCM formula for “strengthening the spleen and tonifying Qi,” particularly in schizophrenia patients with spleen-deficiency patterns. Materials and Methods: We conducted a comprehensive synthesis of available literature focusing on the TCM theoretical foundations, modern pharmacological studies, and clinical evidence related to SJZT in the context of schizophrenia. Both historical TCM texts and contemporary research from electronic databases were analyzed to integrate traditional perspectives with current scientific insights. SJZT demonstrates multi-target pharmacological actions, including immunomodulation, neuroprotection, and gut microbiota regulation, which align with key pathophysiological mechanisms of schizophrenia, such as neuroinflammation and dysregulation of the gut-brain axis. Preliminary clinical observations suggest that SJZT may improve negative symptoms and enhance tolerance to antipsychotic drugs in spleen-deficiency patients. However, robust clinical evidence remains limited, and further high-quality studies are needed. SJZT represents a promising complementary approach for schizophrenia, especially in patients presenting spleen-deficiency patterns. Its multi-component, multi-target mechanisms offer a holistic strategy that addresses limitations of conventional antipsychotics. Future research should prioritize well-designed clinical trials and mechanistic studies to validate efficacy, optimize treatment protocols, and facilitate integration into modern psychiatric practice.
Keywords: Si-Jun-Zi Tang; Schizophrenia; Spleen-Deficiency with Phlegm Obstruction.